2012
DOI: 10.1186/1743-422x-9-78
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in children hospitalized for acute lower respiratory tract infection in Ghana

Abstract: BackgroundAcute respiratory tract infections are one of the major causes of morbidity and mortality among young children in developing countries. Information on the viral aetiology of acute respiratory infections in developing countries is very limited. The study was done to identify viruses associated with acute lower respiratory tract infection among children less than 5 years.MethodNasopharyngeal samples and blood cultures were collected from children less than 5 years who have been hospitalized for acute l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
84
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 40 publications
18
84
4
2
Order By: Relevance
“…These results are in concordance with previous studies from Ghana [17] and Saudi Arabia [19], in which adenovirus was the second most frequently detected virus following RSV infection. However, other studies carried out in Saudi Arabia [18,20] showed that parainfluenza was the second most frequently detected virus following RSV.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in concordance with previous studies from Ghana [17] and Saudi Arabia [19], in which adenovirus was the second most frequently detected virus following RSV infection. However, other studies carried out in Saudi Arabia [18,20] showed that parainfluenza was the second most frequently detected virus following RSV.…”
Section: Discussionsupporting
confidence: 93%
“…Viral infections occurred mostly in children one year of age and younger (88.9%), followed by children between one and five years of age (7.9%) and children over five years of age (3.2%). This is consistent with the age distribution of viral ALRI reported in developing countries [15][16][17][40][41][42][43] and Middle Eastern countries [18,20,24]. However, we did not identify a significant association between PLOS and the type of virus or seasonality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Many respiratory viruses show definite seasonal variation, such as RSV [18], HMPV, influenza [19] and PIV, with peaks during winter [20]. A rise in SIDS cases has been documented in certain populations where infections are frequent, including during colder climates and annual influenza outbreaks [21,22,23].…”
Section: The Burden Of Respiratory Diseasementioning
confidence: 99%